Quaternary gas hydrate dissociation promotes the formation of Shenhu Canyon Group in the South China Sea - Hui Pan; Hui Pan; Hui Xie; Hui Xie; Hui Xie; Zhongxian Zhao; Jinlong Liu; Guozhong Jiang; Guozhong Jiang; Ruilong Li; Yuanping Li; Eun Young Lee; et al. (Frontiers in Marine Science)
The Baiyun deepwater region (Shenhu area) of the Pearl River Mouth Basin (PRMB), northern South China Sea (SCS), is characterized by the presence of abundant gas hydrate deposits and dense submarine canyons. However, the relationships between gas hydrate decomposition and formation of submarine canyons remain unclear. Based on the seismic and well data, the variations of the gas hydrate stability zone (GHSZ) thickness were quantitatively calculated. The results indicate that the thickness of the GSHZ, which ranges from 0 to 350m, is distributed in areas where the water depth exceeds 600m. Since ~2.5 Ma, there have been three combinations of sea level and bottom water temperature (BWT) changes that can significantly reduce the thickness of the GHSZ. These combinations have exerted control over the GHSZ thickness in this region: (1) a slight increase in sea level accompanied by a rapid increase in BWT; (2) a rapid decrease in sea level but a slight decrease in BWT; (3) a rapid increase in both sea level and BWT. It has been found that water depth exerts an influence on the variation of the thickness of GHSZ. The impact in shallow water areas (< 1000m) is more significant than that in deep water areas (> 1000m). Consequently, in the Shenhu area, where the water depth ranges from 500 to 1000 m, the reduction in the thickness of GHSZ is consistently much greater than that in deep water areas. It is hypothesized that during seawater warming or seal level dropping, the substantial decrease in the thickness of GHSZ in the Shenhu area leads to the dissociation of gas hydrates. This dissociation may have triggered methane seepage, resulting in the formation of pockmarks. The pockmarks likely weaken the slope sediments, and the subsequent rapid sea level fall promotes synchronous gravity erosion processes, thereby forming a chain of pockmarks (channel). Continuous gas seepage may further trigger slope failures, which can widen the channel. It is proposed that this iterative process contributes to the formation of the current Shenhu Canyon Group. Our study presents a plausible mechanism elucidating how the reduction in the thickness of GHSZ, the release of methane, and the formation of submarine pockmarks interact to influence and reshape the slope morphology, as well as drive the evolution of submarine canyons. This integrative analysis not only uncovers the complex geological processes at play in the study area but also offers valuable insights into the long term geomorphological development in submarine environments.